Investigating writing difficulties in essay writing: Tertiary students’ perspectives - Bulqiyah, Suhaimah; Mahbub, Moh. Arif; Nugraheni, Dyah Ayu (Universitas Ahmad Dahlan, 2021)
This study is primarily designed for investigating the tertiary students’ perspectives on the writing difficulties of essays. This study was conducted in explanatory research in which quantitative and qualitative data were obtained from the web-based questionnaire and semi-structured interview, then analyzed separately. 21 undergraduate students have enrolled in the survey and 6 of them were invited to the interview section. This research reveals tertiary students' problems in essay writing course are categorized into: affective problems which raise from students’ and lecturers’ attitude while teaching and learning Essay Writing Course, cognitive problems that considered as the difficulties in the areas of writing viewpoint, transferring language, and the process of writing, and linguistic problems in the area of lexico-grammar, vocabulary, and the structure of the essay. Due to the findings, those aspects of academic writing should be serious attention for both EFL students and teachers to overcome the problems. The findings of this study have implications for EFL writing course designers as basic data of material improvement and for researchers particularly in the realms of language and education.